Las estrategias metodológicas y su relación con el desarrollo del lenguaje oral de las niñas y niños de educación inicial del nivel ii de la unidad educativa “Ciudad de Ibarra”, del cantón Joya de los Sachas, provincia de Orellana. Período lectivo 2013-2014”. Lineamientos alternativos - Herrera Sinche, Ester Charito (2015)
This thesis refers to " METHODOLOGICAL STRATEGIES AND ITS RELATION TO THE DEVELOPMENT OF ORAL LANGUAGE OF GIRLS AND CHILDREN OF PRESCHOOL EDUCATION LEVEL OF EDUCATION UNIT II " CITY IBARRA " JEWEL OF THE CANTON SACHAS , PROVINCE Orellana . LECTIVO PERIOD 2013-2014 " . ALTERNATIVE GUIDELINES , made according to the provisions of the Regulation of Academic Board of the National University of Loja. Raised as General Objective: Determine the ratio of the Methodological Strategies and Development of Oral Language of boys girls Early Childhood Education, Level II, Educational Unit "City of Ibarra ," Canton Jewel of Sachas , Province Orellana. The methods used for the preparation of this research work were : Scientist, Inductive- Deductive , Analytic - Synthetic, Model Description and Statistical Method , which served them help efficiently achieve the goal. The techniques and instruments used were: Survey that was applied to early education teachers , Level II Education Unit "City of Ibarra ," to establish the Methodological Strategies used in daily work with children and an Observation that children at the Early Childhood Education , Level II Education Unit " Ibarra City " was applied to determine the Oral Language Development . We conclude that : 100% of the teachers surveyed indicated that the type of Methodological Strategies Used in Everyday Work Day with children from early education level II are strategy discovery and inquiry , 67% of project strategy ; and 33% strategy of problematization. 57% of girls and children have seen Oral Language Development Highly Satisfactory , Satisfactory 39% ; and 4% Unsatisfactory . The basic means of human communication is oral language , voice and speech that allow the individual to express their thoughts , ideas , knowledge and activities. In Manual of Oral Language Development delivered to the directors of the Educational Unit "City of Ibarra ," Joya canton of Sachas , Orellana Province. , Is intended to help to improve the application of the Methodology for Development Strategies Oral language of children .